Early administration of renin–angiotensin system inhibitors improves survival and cardiac remodeling in heart failure with preserved ejection fraction - Yuka Kono; Kunihiro Sonoda; Kazuo Ohtake; Akinobu Ota; Shusei Yamamoto; Hinako Nakayama; Taketo Fukuoka; Yuki Kawai; Haruka Tago; Nobuhisa Watanabe; Ikumi Sato; Satoshi Hirohata; et al. (PLoS ONE, 2026)
Heart failure with preserved ejection fraction (HFpEF) is a major cardiovascular disease that accounts for 50% of all cases of heart failure. Patients with HFpEF have limited therapeutic options because of the complex pathogenesis of this disease. Decreased nitric oxide (NO) levels and increased renin–angiotensin system (RAS) activity may be associated with HFpEF pathogenesis. However, whether soluble guanylate cyclase (sGC) stimulators and RAS inhibitors protect against HFpEF remains unclear. This study aimed to evaluate the preventive effects of RAS inhibitors captopril (Cap) and/or sacubitril/valsartan (Sac/Val) and sGC stimulator vericiguat (Ver) on HFpEF progression. HFpEF was induced in 8-week-old male Wistar rats through intake of L-arginine methyl ester and a high-fat diet. Results showed that the survival rate after 8 weeks of treatment was 100% in the normal diet (Cont group), Cap, and Sac/Val groups, whereas it was approximately 20% in the HFpEF and Ver groups. No significant differences in the left ventricular systolic function were found. In addition, histochemistry revealed that myocardial hypertrophy and interstitial fibrosis obviously increased in the HFpEF group but not in the Cap and Sac/Val groups compared with the Cont group. Furthermore, RNA sequencing analysis showed that the expression of genes related to inflammatory response, hypertrophy, and extracellular matrix–receptor interaction increased in the HFpEF group and decreased in the Cap and Sac/Val groups. In conclusion, early administration of Cap or Sac/Val may reduce the risk of developing HFpEF by inhibiting the RAS pathway rather than the NO-sGC-cGMP pathway.